Inclusive Tawhid as an Epistemology of Islamic Education - Gaffar, Abdul; Anees, Muhammed (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2025)
doctrine but as a basic epistemology in Islamic education that encourages reflective awareness and pluralistic values. By integrating the philosophical-anthropological dimensions of humans as 'abd Allah and khalīfah fī al-ardh, inclusive tawhid views humans as unfinished beings who need mujahadah, spiritual and intellectual struggle through a meaningful educational process. Amid global challenges such as Islamophobia, ideological polarization, and identity crisis in a multicultural society, inclusive tawhid offers a transformative education model that builds solidarity based on universal spirituality, not doctrinal uniformity. This research uses an exploratory qualitative approach with a comprehensive literature study of scientific publications related to inclusive tawhid-based Islamic education. Data were collected from accredited journal articles, academic books, and public secondary sources, then thematically analyzed to identify patterns, values, and philosophical foundations in the discourse of inclusive Islamic education. The results show that inclusive tawhid is a strong epistemological basis for reconstructing a more dialogic, tolerant, and humanistic Islamic education paradigm. In addition, this study emphasizes the urgency of reforming the national curriculum to be more sensitive to religious and cultural plurality and to get out of the normative-liberal and conservative-literal dichotomy. This study provides a theoretical contribution to the philosophy of Islamic education and a strategic foundation for curriculum development based on universal ethical and spiritual values.